Aplicación de la norma técnica del crecimiento y desarrollo en el menor de 10 años en el componente de detección temprana de las alteraciones visuales y oculares (2024)
According to the Colombian concept, early childhood is understood as the first stage of life. included from birth to 6 years of age, this developmental process being human, the critical period between the acquisition of new skills and abilities allowing a normal, consecutive and successful evolution that grants the infant quality of life without limitations (1)